{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

math117_assignment03

# math117_assignment03 - Math 117 Assignment#3 Fall 2008 due...

This preview shows pages 1–2. Sign up to view the full content.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Math 117 Assignment #3 - Fall 2008 due October 2nd or 3rd - A/ Suggested Problems: Adams §P.7 # 1—30, §3.5 # 1—16, §3.6 #7ab. B / For Submission: 1. Adams, §P.7 #13,15. 2. Adams, §3.5 # 13,15,17 (see Example 3, p.189) 3. Rewrite the following expressions in the form of a single sine function (of the form r sin(l9 — (1)): a) sin 6 + 8 cos 0 b) 3 cos (9 — sin 0. 4. You may have been introduced to the hyperbolic functions in class. These are deﬁned as the even and odd components of the natural exponential function: ex + 6"“5 ex — e“ coshz= ————-, sinhx= —— 2 2 (You can see that cosh z is even, sinhz is odd, and cosh cc + sinh a: = ex.) From these deﬁnitions, show that a) sinh(:r + y) = sinh :1: cosh y + cosh z sinh y b) sinh(3\$) = 3 sinh z + 4 sinh3 2:. In fact, the hyperbolic functions obey a set of identities very similar to that of the trigonometric functions. To obtain one from the other, we-simply change the sign of every product of two Sines; this is “Osborn’s Rule”. cos2 x + sin? cc = 1 ——> cosh2 a: — sinh2 :1: = 1 1 + tan2 z = 3602.73 ——> 1 — tanh2 z = sech2\$ cos(z + y) = cos ac cosy —— sin a: sin y ——> cosh(a: + y) = cosh a; cosh y + sinh zsinh y cos2z= -21;(1+cos2z) ——>cosh2z= %(1+cosh2m) etc. Math 117 — Assignment #3 Page 2 5. Consider the function f (:13) = 3:3 + x. This is a one-to—one function (this should be obvious, if you think of what the graph must look like), so we know it must have an inverse, but it isn’t obvious that there’s a convenient way to write it. Surprisingly, the hyperbolic sine function can help, because of one of the identities above. Follow these steps to ﬁnd f ‘1: L“ y = 173 + 9:. Then set z = ‘99:, and show that 4z3 + 3z = #9 Now let 2 = sinh 6, and apply the identiy you proved in #4b above. You can then solve for 6, and reverse the changes of variables to ﬁnd :1: as a function of y. ...
View Full Document

{[ snackBarMessage ]}

### Page1 / 2

math117_assignment03 - Math 117 Assignment#3 Fall 2008 due...

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online